# Write 6(x – 5)^{4} + 4(x – 5)^{2} + 6 = 0 in the form of a quadratic by using substitution.

Higher polynomial functions can be simplified using the substitution method and further converting to quadratic form.

## Answer: The reduced expression for 6(x – 5)^{4} + 4(x – 5)^{2} + 6 = 0 can be written as 6t^{2} + 4t + 6 = 0 in the quadratic expression form.

Go through the step-by-step solution, to find the exact solution.

**Explanation:**

Let (x - 5)^{2 }= t

Thus, the given expression reduces to the form:

⇒ 6t^{2} + 4t + 6 = 0